Effect of Lumber Quality Grade on the Mechanical Properties and Product Costs of Cross-Laminated Timber Panels - Mahmut M. Bayramoglu; Aydın Demir; Abdullah Uğur Birinci; Hasan Ozturk; Okan İlhan; Zeki Candan; Cenk Demirkir (BioResources)
This study aimed to investigate the effects of wood species and lumber quality grades on the mechanical properties and costs of cross-laminated timber (CLT) panels. Various combinations of lumber with different quality grades were utilized in the layers to identify the optimal configurations for producing CLT panels with high mechanical performance and low costs. In the study, spruce and Scots pine lumber of three different quality grades (Grades 1, 2, and 3), classified according to TS 1265 standards, were used. Some mechanical properties of the CLT panels produced from lumber of varying quality grades were determined following the TS EN 408 standard. Additionally, cost analyses of the CLT panels were conducted based on the calculation of raw material costs. The results show that while higher-grade lumber improves mechanical performance, lower-grade combinations still can meet structural needs at lower costs. Mixed-grade configurations offer a balance between strength and affordability. These findings can help CLT producers optimize material selection and reduce costs while maintaining structural integrity. Using lower-grade lumber can address shortages and reduce reliance on expensive timber. Policymakers can promote sustainable forestry and lower production costs, making mass timber construction more viable and environmentally sustainable.